University Lecturers’ and Students’ Perceptions and Use of Genai Technologies - Chen Zheng; Kee Chye Leo; Rachel Sheffield; Nicole Fairhurst (Tecno Scientifica Publisher, 2026)
ChatGPT, Bard, and other generative artificial intelligence (GenAI) technologies, also known as conversational AI or chatbots, were trained to be informative and comprehensive. This definition described the capacity of GenAI to answer, create, and complete tasks, such as writing essay responses using user-generated prompts. Universities were often unsure of how to incorporate this technology into the teaching and learning process in a consistent and ethical manner. There was debate about the positive and negative aspects of GenAI within universities, such as prompt feedback and resource development, versus breaches of academic integrity. The inconsistencies in messaging and debates led both academics and students to feel anxious, confused, and concerned. This project explored the expertise, confidence, and subsequent experiences of university students and academics with the use of GenAI technologies in their teaching, learning, and assessment. It employed a mixed-methods approach, combining a quantitative survey with qualitative interviews conducted across international campuses of a large public university, with a sample of 132 students and 38 staff. GenAI had the potential to enhance productivity and efficiency in education; however, further support and clarification were needed to foster the development of critical skills for evaluating information output and the ethical use of these technologies.